Combined epidemiological and genomic analysis of nosocomial SARS-CoV-2 infection early in the pandemic and the role of unidentified cases in transmission. (January 2022) - Snell, Luke B.; Fisher, Chloe L.; Taj, Usman; Stirrup, Oliver; Merrick, Blair; Alcolea-Medina, Adela; Charalampous, Themoula; Signell, Adrian W.; Wilson, Harry D.; Betancor, Gilberto; Kia Ik, Mark Tan; Cunningham, Emma; et al.
Abstract: Objectives: To analyse nosocomial transmission in the early stages of the coronavirus 2019 (COVID-19) pandemic at a large multisite healthcare institution. Nosocomial incidence is linked with infection control interventions. Methods: Viral genome sequence and epidemiological data were analysed for 574 consecutive patients, including 86 nosocomial cases, with a positive PCR test for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during the first 19 days of the pandemic. Results: Forty-four putative transmission clusters were found through epidemiological analysis; these included 234 cases and all 86 nosocomial cases. SARS-CoV-2 genome sequences were obtained from 168/234 (72%) of these cases in epidemiological clusters, including 77/86 nosocomial cases (90%). Only 75/168 (45%) of epidemiologically linked, sequenced cases were not refuted by applying genomic data, creating 14 final clusters accounting for 59/77 sequenced nosocomial cases (77%). Viral haplotypes from these clusters were enriched 1–14x (median 4x) compared to the community. Three factors implicated unidentified cases in transmission: (a) community-onset or indeterminate cases were absent in 7/14 clusters (50%), (b) four clusters (29%) had additional evidence of cryptic transmission, and (c) in three clusters (21%) diagnosis of the earliest case was delayed, which may have facilitated transmission. Nosocomial cases decreased to low levels (0–2 per day) despite continuing high numbers of admissions of community-onset SARS-CoV-2 cases (40–50 per day) and before the impact of introducing universal face masks and banning hospital visitors. Conclusion: Genomics was necessary to accurately resolve transmission clusters. Our data support unidentified cases—such as healthcare workers or asymptomatic patients—as important vectors of transmission. Evidence is needed to ascertain whether routine screening increases case ascertainment and limits nosocomial transmission.